REPRESENTATIONS OF TRANSGENDER CHARACTERS IN INDIAN AND AMERICAN LITERATURE AND MEDIA – STEREOTYPING VERSUS EMPOWERED PORTRAYALS - Rafiq, Anam; Sehrawat, Anil; Singh, Bijendra (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper explores the evolving representations of transgender individuals in Indian and American literature and media, focusing on the tension between stereotypical and empowered portrayals. Drawing upon queer theory, postcolonial perspectives, and media studies, the analysis contextualizes how cultural, historical, and legal factors have shaped these narratives. In India, colonial legacies and the socio-religious status of Hijra communities inform depictions that oscillate between mythic reverence and marginalization. In contrast, American media, influenced by individualistic frameworks and LGBTQ+ activism, grapples with issues of visibility and authenticity, often constrained by sensationalized stereotypes. Across both contexts, portrayals of transgender characters have historically leaned on tropes such as the “comic relief” or the “tragic victim,” perpetuating stigma and misinformation. Yet, a discernible shift is underway: contemporary works, including autobiographical literature, documentaries, and critically acclaimed films, increasingly grant transgender characters depth, agency, and complexity. These empowered narratives challenge harmful assumptions, promote empathy, and contribute to broader social acceptance and legal recognition. By comparing Indian and American contexts, this study highlights the transformative potential of inclusive storytelling and underscores the ongoing need for authentic transgender voices in authorship and production. The paper concludes that while progress has been made, continued advocacy and structural reforms in the media industries are essential for fostering more nuanced and affirming representations.